Real-time Depth of Field using Multi-Layer Filtering - Selgrad, Kai; Reintges, Christian; Penk, Dominik; Wagner, Pascal; Stamminger, Marc (Proceedings of the ACM SIGGRAPH Symposium on Interactive 3D Graphics and Games 2015, 2015)
We present a novel technique for rendering depth of field that addresses difficult overlap cases, such as close, but out-of-focus, geometry in the near-field. Such scene configurations are not managed well by state-of-the-art post-processing approaches since essential information is missing due to occlusion. Our proposed algorithm renders the scene from a single camera position and computes a layered image using a single pass by constructing per-pixel lists. These lists can be filtered progressively to generate differently blurred representations of the scene. We show how this structure can be exploited to generate depth of field in real-time, even in complicated scene constellations.
UnivIS-Import:2015-04-17:Pub.2015.tech.IMMD.IMMD9.realti
Keywords: GRK-1773